ADAPTASI ALAT UKUR MINAT MENELITI - Immanuel Yosua; Desty Lovina; Dessy Eka Purnama; Benedicta P. Dwi Riyanti; Magdalena S. Halim (JURNAL PSIKOLOGI INSIGHT, 2018)
This study aimed to adapt the measurement of Interest in Research developed by Bishop and Bieschke (1998). This development is necessary to map the potential of lecturers in research interest. This further will be useful for the development of programs or policies that facilitate the increasing of lecturer interest towards research. The measurement tools that have been adapted here, comprising Research Self-Efficacy and Interest in Research. Based on previous finding, these two were more significant in predicting Research Productivity (Bieschke, Herbert, and Bard, 1998). The development of these measurements was analyzed by the construct validity testing, criterion-based validity testing, and reliability testing. The result of the construct validity testing of the Research Self-Efficacy by using Explanatory Factor Analysis (EFA) has exhibited three dimensions namely: Research Implementation, Research Planning, and Research Teamwork. The result of criterion-based validity testing has indicated a significant positive correlation between Research Self-Efficacy and Research Productivity (0.321) and between Interest in Research and Research Productivity (0.229). Whilst the result of reliability testing has indicated that both measuring instruments have high reliability, that is equal to 0.981 for Research Self-Efficacy, and 0.953 for Interest in Research.